Measuring the Effectiveness of Classroom Presentations and their Impact on Students’ Motivation for Fluent Speaking Performance - ZELLOUMA, Ahmed (Journal of Human Sciences, 2018)
Speaking is often believed to be the most paramount language skill. Thus, teachers of Oral Expression in the different universities work very hard to enhance their students’ self-expression. One of the most prevailing ways of doing so is via oral presentations. This research paper investigates the influence of this classroom strategy on students’ motivation for the course of Oral Expression and its effectiveness in developing their speaking skill. The results of this study, which was conducted on 210 second year students of English in the university of El-Chahid Hamma Lakhdar in El-Oued, and 40 teachers of Oral Expression from different Algerian universities, come to validate the hypotheses we set at its beginning: (a) oral presentations, which are being currently done in most Algerian universities, do not respect the common standards of public speaking and oral presentations. Also, (b) these oral presentations have a demotivating impact on students’ desire to attend and participate in the Oral Expression sessions. Besides, (c) they do not improve students’ speaking skill significantly. Last, (d) if students were taught an innovative course of oral expression sessions following the Communicative Approach to language teaching; then their motivation to the subject would increase significantly and their speaking skill would improve in general.